Intersubject specific absorption rate variability analysis through construction of 23 realistic body models for prostate imaging at 7T - Meliadò, Ettore F.; van den Berg, Cornelis A.T.; Luijten, Peter R.; Raaijmakers, Alexander J.E. (Magnetic resonance in medicine, 2019)
Purpose For ultrahigh field (UHF) MRI, the expected local specific absorption rate (SAR) distribution is usually calculated by numerical simulations using a limited number of generic body models and adding a safety margin to take into account intersubject variability. Assessment of this variability with a large model database would be desirable. In this study, a procedure to create such a database with accurate subject‐specific models is presented. Using 23 models, intersubject variability is investigated for prostate imaging at 7T with an 8‐channel fractionated dipole antenna array with 16 receive loops. Method From Dixon images of a volunteer acquired at 1.5T with a mockup array in place, an accurate dielectric model is built. Following this procedure, 23 subject‐specific models for local SAR assessment at 7T were created enabling an extensive analysis of the intersubject B1+ and peak local SAR variability. Results For the investigated setup, the maximum possible peak local SAR ranges from 2.6 to 4.6 W/kg for 8 × 1 W input power. The expected peak local SAR values represent a Gaussian distribution (μ/σ=2.29/0.29 W/kg) with realistic prostate‐shimmed phase settings and a gamma distribution Γ(24,0.09) with multidimensional radiofrequency pulses. Prostate‐shimmed phase settings are similar for all models. Using 1 generic phase setting, average B1+ reduction is 7%. Using only 1 model, the required safety margin for intersubject variability is 1.6 to 1.8. Conclusion The presented procedure allows for the creation of a customized model database. The results provide valuable insights into B1+ and local SAR variability. Recommended power thresholds per channel are 3.1 W with phase shimming on prostate or 2.6 W for multidimensional pulses.